GIP/GLP-1 DUAL AGONIST TIRZEPATIDE AMELIORATES RENAL ISCHEMIA/REPERFUSION DAMAGE IN RATS - ALKHAFAJI, GHADA A.; JANABI, ALI M. (International Journal of Applied Pharmaceutics, 2025)
Objective: Renal Ischemia/Reperfusion Injury (RIRI) initiates a cascade of deleterious events resulting in acute kidney injury with high mortality rates. Tirzepatide has anti-inflammatory, anti-apoptotic and antioxidant as well as activation of both autophagy and Protein Kinase B (PKB or Akt) signaling pathway. This study examines the potential nephroprotective effect of tirzepatide against RIRI in rats. Methods: Twenty-eight male rats (Sprague Dawley) were split into four groups: sham, Ischemia/Reperfusion Injury (IRI), Distilled Water (D. W) and tirzepatide. The Sham group underwent identical procedures without bilateral renal pedicle clamping, whereas IRI group was exposed to 30 min of bilateral renal ischemia followed by 24 h of reperfusion. The vehicle group received distilled water intraperitoneally 2 h before ischemia, and the tirzepatide group received 3 mg/kg tirzepatide intraperitoneally 2 h before ischemia. Study parameters including urea, creatinine, Kidney Injury Molecule-1 (KIM-1), interleukin-6 (IL-6), caspase-3, Akt, autophagic protein microtubule-associated protein 1 light chain 3-B (LC3-B) and glutathione (GSH), and histopathological changes were examined. Results: RIRI resulted in a significant elevation in serum urea, serum creatinine and renal levels of KIM-1, IL-6, caspase-3, Akt, and LC3-B while a concurrently reduction in renal GSH level. Tirzepatide treatment diminished the severity of kidney damage by alleviating inflammatory apoptotic and autophagy markers, augmenting antioxidant activity and improving histopathological consequences. Conclusion: Tirzepatide elucidates significant nephroprotective effects in RIRI, via its anti-inflammatory, antioxidant, and antiapoptotic properties and activation of both autophagy and Akt signaling pathway.